TANGGUNG JAWAB DIREKSI DAN KOMISARIS PERSEROAN TERBATAS PAILIT DIKAITKAN DENGAN UTANG PAJAK - Citra Valentina Nainggolan; Budiman Ginting; Sunarmi Sunarmi; Utari Maharany Barus (USU LAW JOURNAL, 2018)
ABSTRACT                     Tax revenues in the state budget in order to fill their coffers national development is very important and very strategic . The role played by such a tax would need to be instilled in everyone for the implementation of tax payments that have been made can be a matter of pride for having contributed to the national development. The problems discussed in this study are as follows First : What is the legal basis for regulation and taxation of the Limited Liability Company ? Second : What is the status of tax debts in bankruptcy Limited Liability Company ? Third : What is the responsibility of directors and commissioners Company Limited against tax liabilities if the Company Limited declared bankrupt ?Type of research is normative juridical research ie legal research done by researching library materials or secondary data consisting of legal materials arranged in a systematic, studied, and then drawn a conclusion in relation to the problems examined . The nature of research is descriptive analytic , descriptive , covering the contents and structure of the positive law , which is an activity undertaken by the authors to determine the content or the meaning of the rule of law referred to in the settlement of legal issues that become the object of study .Data collection method used is the method library (library research ) literature that is data obtained through library research sourced from laws, official documents,book, and research results .The results showed that , first : There is already a clear and unequivocal arrangements regarding the taxation of the company as legal entities that are required to meet those conditions. Second: The tax debt prior to the issuance of the decision No. 67 / PUU - XI / 2013 is a special priority of creditors other than those prescribed by Article 21 point ( 3 ) Law number 28 of 2007 on general provisions and taxation procedures , shifted its position in the payment of the debt after payment of wages / labor due in advance. Third : Vice taxpayer ( directors and commissioners ) is the personal responsibility or successively on the payment of taxes owed. Keywords: Directors , Commissioners , Bankruptcy , Tax Debt